Effect of midazolam premedication on the dose of propofol for laryngeal mask airway insertion in children - Priyesh Bhaskar; Anita Malik; Rajni Kapoor; Monica Kohli; Jyotsana Agarwal; Mamta Harjai (Wolters Kluwer Medknow Publications, 2010)
Background: The present study was conducted on 120 pediatric patients of ASA Grade I and II of either sex aged 3-12 years scheduled for pediatric surgeries under general anaesthesia. Patients & Methods: All patients were randomly divided into Group A and Group B. Group A was further divided into 3 subgroups of unpremedicated patients who received 3, 4 and 5 mg kg -1 propofol only designated as A1, A2 and A3 respectively. Group B was further divided into subgroups of premedicated patients with midazolam (0.05 mg kg -1 ) intravenous and received 3, 4 and 5 mg kg -1 propofol designated as B1, B2 and B3 respectively. Results: Results showed that increasing dose of propofol decreases the adverse events like inadequate jaw relaxation, limb movements, coughing, gagging and laryngospasm. Midazolam when added to propofol further reduces the incidence of adverse events and provides more favorable environment for insertion of LMA. At higher doses of propofol (5 mg kg -1 ), hypotension is a major problem due to its cardiovascular depressant action. Therefore, 4 mg kg -1 propofol along with midazolam is the optimum dose because there is more hemodynamic stability and we get better conditions for LMA insertion. Conclusion: Midazolam is an effective premedication in children which is synergistic with propofol and reduces its effective dose, required for LMA insertion.